O roli (ochrony) praw człowieka z perspektywy międzynarodowego sądownictwa karnego - Krzan, Bartłomiej (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article deals with the increased interplay between human rights and international criminal law. Traditionally, the gravest human rights violations would fall within the subject-matter of international jurisdiction of international crimes. Upon a closer look, however, one may also identify the reverse direction of influence. From this perspective, respect for human rights may significantly contribute to the legitimacy of international tribunals exercising jurisdiction in criminal matters. Against this background the proceedings of international military tribunals, ad hoc tribunals and the permanent International Criminal Court are scrutinized. In this regard, one may juxtapose the very modest interest in respecting the defendants’ rights before the tribunals established after World War II, while the statutes of the subsequently created judicial institutions addressed the issues in a more in-depth manner. The jurisprudence of those tribunals has been also taking into account the work of human rights instruments and monitoring bodies, including the European Court of Human Rights. Special attention is paid to the Rome Statute and the practice of the International Criminal Court, and in particular to the reference to “internationally recognized human rights”, as referred to in Article 213 of the Rome Statute and applied in the hitherto practice of the permanent Court.
Keywords: ochrona praw człowieka; międzynarodowe sądownictwo karne